2003
DOI: 10.1097/00126334-200306010-00018
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection and Associated Risks Among Young Men Who Have Sex With Men in a Florida Resort Community

Abstract: The high prevalences of UAI and HIV infection in South Beach attest to a previously undocumented public health concern. The extremely high estimated incidence for young MSM in South Beach highlights the urgent need for more effective risk-reduction interventions and further epidemiological research on resort areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 32 publications
2
34
0
1
Order By: Relevance
“…Researchers and public health officials have employed an array of approaches to behavioral surveillance, including sentinel surveillance; RDD studies; and, venue-based sampling [2,8,[10][11][12][13][14][15][16][17][18]. Each approach has its advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers and public health officials have employed an array of approaches to behavioral surveillance, including sentinel surveillance; RDD studies; and, venue-based sampling [2,8,[10][11][12][13][14][15][16][17][18]. Each approach has its advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers and public health officials have developed an array of behavioral surveillance programs [2,8,[10][11][12][13][14][15][16][17][18], few population-based data are available to assess trends in risk among MSM, the group at highest risk for HIV infection in the US and many other nations [3,19]. We present an analysis of serial random digit dial surveys conducted among MSM in Seattle, Washington in 2003 and 2006.…”
Section: Introductionmentioning
confidence: 99%
“…However, geographically concentrated urban populations of MSM probably are common across the United States, and our sample resembles probability samples of MSM in other cities in the pre-HAART era on several demographic characteristics. [41][42][43] Furthermore, response rates in RDD telephone surveys tend to be lower than those obtained in household surveys conducted face-to-face. Nonetheless, the 46% response rate we observed approximates that for other RDD telephone surveys such as the national 2003 Survey of Consumer Attitudes (48%) 44 and the 2002 Behavioral Risk Factor Surveillance Survey in Washington state (54%), which was carried out by the same telephone survey firm that collected our data.…”
Section: Sexual Behavior In Msmmentioning
confidence: 99%
“…In some countries like Switzerland (Dubois-Arber et al, 2002) and Spain (Pérez et al, 2002) HIV-testing rates among MSM of approximately 80% have been reported. In MSM samples in Australia (National Centre in HIV Social Research, 2003) and the USA (Webster et al, 2003) rates of over 90% have been observed. In other Western countries, such as the Netherlands and Scotland, HIV-testing rates among MSM are substantially lower.…”
Section: Introductionmentioning
confidence: 99%